Large deviations for non-zero initial conditions in linear systems. (December 2016) - Polyak, Boris T.; Smirnov, Georgi
Abstract: Transient response of linear systems with non-zero initial conditions was at the center of attention for engineers and researchers at early stages of classical control theory. However this field was not intensively investigated later. For instance, the breakthrough result on unavoidable peaking effect for systems with strong damping factor was obtained by Izmailov in 1987, but it did not attract much attention. We try to continue this line of research and provide explicit worst-case lower bound. Then we exhibit large deviation effects for other pole locations and estimate lower bounds for them. The upper bounds for deviations of trajectories are much better studied; to obtain the smallest deviations by static linear feedback the techniques of linear matrix inequalities can be exploited. We demonstrate that for such closed-loop systems the upper and lower bounds have the same asymptotic behavior.